2021
DOI: 10.3390/molecules26041079
|View full text |Cite
|
Sign up to set email alerts
|

Heterocyclic Substitutions Greatly Improve Affinity and Stability of Folic Acid towards FRα. an In Silico Insight

Abstract: Folate receptor alpha (FRα) is known as a biological marker for many cancers due to its overexpression in cancerous epithelial tissue. The folic acid (FA) binding affinity to the FRα active site provides a basis for designing more specific targets for FRα. Heterocyclic rings have been shown to interact with many receptors and are important to the metabolism and biological processes within the body. Nineteen FA analogs with substitution with various heterocyclic rings were designed to have higher affinity towar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
26
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 22 publications
(28 citation statements)
references
References 77 publications
2
26
0
Order By: Relevance
“…ASP81 form two strong H-bonds with FA-βCD; one with a pteridine ring at N5 at a distance of 2.01Å and the other with N7 (1.84 Å) (Figure 7b). This observation is consistent with previous studies that showed that ASP81 interacted with the pteridine ring and is considered as a key contributor to the high folate affinity [26,27,30]. In FA-FRα (Figure 7a), two H-bonds were also observed between the pteridine ring with ASP81 (1.93 Å and 2.15 Å).…”
Section: Molecular Dynamics (Md) Simulation 221 Stability Of the Simulated Systemssupporting
confidence: 92%
See 4 more Smart Citations
“…ASP81 form two strong H-bonds with FA-βCD; one with a pteridine ring at N5 at a distance of 2.01Å and the other with N7 (1.84 Å) (Figure 7b). This observation is consistent with previous studies that showed that ASP81 interacted with the pteridine ring and is considered as a key contributor to the high folate affinity [26,27,30]. In FA-FRα (Figure 7a), two H-bonds were also observed between the pteridine ring with ASP81 (1.93 Å and 2.15 Å).…”
Section: Molecular Dynamics (Md) Simulation 221 Stability Of the Simulated Systemssupporting
confidence: 92%
“…It is noted that the βCD did not enter the binding site, and only formed an interaction with the amino acid at the surface of FRα such as LYS19. Interestingly, conjugation to βCD resulted in the FA to elude its H-bonds interaction between its glutamic acid moiety with LYS136, GLY137, TRP138, and TRP140, a behaviour observed in our previous study [27]. In addition, Figure 3b shows that the residue TYR85 lost its π-π stacking interaction with the pteridine ring from the FA structure of the FA-βCD.…”
Section: Molecular Docking Analysissupporting
confidence: 56%
See 3 more Smart Citations